1983
DOI: 10.1002/jsfa.2740340307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extracts from bean (phaseolus vulgaris) and field bean (vicia faba) varieties on intestinal D‐glucose transport in rat in vivo

Abstract: Saline extract solutions from seeds of both Phaseolus vulgaris and Vicia faba varieties were prepared and tested for their total polyphenolic content and effect on intestinal D-Glucose transport across rat ileum in viva. Intestinal D-ghCOSe transport was significantly reduced (P< 0.001) by the presence of seed-extracts in the intestinal loop, regardless of the source of the extract. The order of potency (Phaseolus vulgaris, var. artropurpurea > Vicia faba, var. caballur > Vicia ,faha, var. minor > Phaseolus vu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 19 publications
3
7
0
Order By: Relevance
“…This was in agreement with results of other in sacco polyphenol experiments [14,[26][27][28] . Generally, in other studies, a dose-dependent decrease of nutrient absorption was recorded.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This was in agreement with results of other in sacco polyphenol experiments [14,[26][27][28] . Generally, in other studies, a dose-dependent decrease of nutrient absorption was recorded.…”
Section: Discussionsupporting
confidence: 83%
“…It was suggested that an inhibition of absorption was a result of protein denaturation on the surface of brush border cells [7] . However, later studies did not observe any alterations on the surface of the intestine of rats perfused with liquid containing bean polyphenols [14] . A potential mechanism of the inhibitory action of polyphenols takes place inside the mucosa and includes a significant dose-dependent decrease of brush border enzymatic activity [10] , the most important of which seems to be a reduction of Na + ,K + pump activity in the mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In-vitro intestinal transport of galactose was also reduced in birds fed on the diets containing tannic acid and in those fed the RKB diet. Similar results have been found in rats and chickens fed on other raw legume diets Santidrian 1981;Motilva et a/ 1983). The mechanism by which this inhibitory effect occurs remains to be completely understood although several hypotheses have been put forward (Mitjavila et al 1970(Mitjavila et al , 1977Ribereau-Gayon 1972).…”
Section: Discussionsupporting
confidence: 81%
“…Care was taken to prepare isoenergetic diets to avoid Using adequate techniques, we reported that the intestinal absorption was diminished in rats on V. faba, which is in reasonable agreement with the elevated values of fecal nitrogen and the decreased urinary nitrogen excretion in these animals [16][17][18].…”
Section: Discussionsupporting
confidence: 55%